Pemahaman Hadis Nabi tentang Spiritualitas dan Moralitas Sebagai Perilaku Keagamaan Generasi Z di Era Modern - Pryditzia Presdiranti; Nasrulloh (Al-Kindi, 2026)
The digital era has had a major impact on the way Generation Z understands and practices Islamic teachings, including the hadith of the Prophet as the second source of teachings after the Qur'an. This study aims to describe how the understanding of hadith about spirituality and morality affects the formation of religious behavior in the modern era generation Z. This study uses a qualitative method with a literature study approach, this study analyzes various relevant literature and scientific sources. The results of the study show that although Generation Z obtains a lot of religious information through digital media, proper understanding of hadith remains an important aspect in building morals, spirituality and religious identity. Hadith about faith, Islam, ihsan, and ethics both play a big role in guiding Generation Z in social life and digital media activities. In addition, understanding hasi also encourages the involvement of Generation Z in social activities and improves the quality of worship. Thus, the hadith of the Prophet remains relevant as a moral and spiritual guideline in shaping the religious behavior of generation Z in the midst of the challenges of modernization and globalization.